2001
DOI: 10.1037/0278-7393.27.3.817
|View full text |Cite
|
Sign up to set email alerts
|

Working memory and focal attention.

Abstract: Measures of retrieval speed indicated that only a small subset of representations in working memory falls within the focus of attention. An n-back task, which required tracking an item 1, 2, or 3 back in a sequentially presented list, was used to examine the representation and retrieval of recent events and how control processes can be used to maintain an item in focal attention while concurrently processing new information. A speed-accuracy trade-off procedure was used to derive measures of the availability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
385
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(423 citation statements)
references
References 82 publications
31
385
2
Order By: Relevance
“…In additional support of this suggestion of an adjustable scope of attention, it recently has been observed that, although one can recognize the most recent item in a presented list more quickly than prior items (McElree, 2001), with practice the advantage expands to the most recent four or so items (Verhaeghen, Cerella, & Basak, in press). The latter result suggests that attention at first must be strongly focused on each item as it is presented but that, with sufficient task familiarity, attention can be focused on the last several items at once.…”
Section: Discussionmentioning
confidence: 92%
“…In additional support of this suggestion of an adjustable scope of attention, it recently has been observed that, although one can recognize the most recent item in a presented list more quickly than prior items (McElree, 2001), with practice the advantage expands to the most recent four or so items (Verhaeghen, Cerella, & Basak, in press). The latter result suggests that attention at first must be strongly focused on each item as it is presented but that, with sufficient task familiarity, attention can be focused on the last several items at once.…”
Section: Discussionmentioning
confidence: 92%
“…An alternative model proposed by McElree was based mainly on examination of the time course of retrieval (McElree, 2001(McElree, , 2006McElree & Dosher, 1989). This model postulates that there are only two representational states: (a) passive representations and (b) a single item in the focus of attention.…”
Section: Instantaneous Retrieval?mentioning
confidence: 99%
“…Access to information held inside the focus of attention is immediate, whereas access to information outside the focus is slower and effortful (e.g., Cowan, 1994Cowan, , 2001. Although estimates of the number of items that can be held in the focus of attention range between one and four, there is strong evidence to indicate only a single item can be held in the focus of attention on the n-back (McElree, 2001;Verhaeghen & Basak, 2005) and n-count (Garavan, 1998) tasks. Therefore, performance in the n-back and n-count conditions where N = 2 requires controlled and effortful switching of attentional focus from one item to another.…”
mentioning
confidence: 99%
“…Specifically, this view predicts that stress will impair effortful or controlled processing but leave intact processing that does not place heavy demands on attentional control. That is, stress should not impair performance that relies on chronically or immediately accessible information but should impair performance that relies on information that lies outside of the focus of attention (Garavan, 1998;McElree 2001;Verhaeghen & Basak, 2005). In a related line of reasoning, Boals (2001a, 2001b) have postulated that stress-related cognitions (i.e., intrusive thoughts, thought suppression) occupy attentional resources and thereby produce deficits in information processing that rely heavily on controlled attention (see also Eysenck & Calvo, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation